Using Inside Job to Teach Business Ethics - Biktimirov, Ernest N.; Cyr, Don J. (2013)
This article recommends the film Inside Job as an effective teaching tool for illustrating the ethical issues that surrounded the global financial crisis of 2008 and the subsequent economic downturn. The study discusses issues such as the revolving door, conflicts of interest, fiduciary duty, executive compensation, and financial regulation. The presentation of each ethical issue comprises suggested questions, background information, and guides to specific sections of the film. An overview of the film is provided as well.
Keywords: Teaching Business Ethics; Revolving door; Inside Job; Financial regulation; Financial Crisis; Fiduciary Duty; Executive Compensation; conflicts of interest